Is Inflation Effective for Liquidating Short-Term Nominal Debt? (IMF Working Papers; Working Paper ;, 1989)
The possibility of reducing the real value of domestic non-indexed government debt through inflation is studied. A central result is that this kind of debt liquidation is possible even though prices are sticky and government bonds are short term. A policy implication is that short bond maturities are no safeguard against surprise devaluations intended to lower the burden of the debt. If devaluation incentives are present, it is further argued that nominal non-indexed bonds could give rise to situations where devaluations are a consequence of self-fulfilling expectations cycles. Any views expressed in the Departmental Memoranda (DM) Series represent the opinions of the authors and, unless otherwise indicated, should not be interpreted as official Fund views.